2010
DOI: 10.1016/j.humov.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

On the cognitive processes underlying contextual interference: Contributions of practice schedule, task similarity and amount of practice

Abstract: This experiment was designed to assess the combined influence of practice schedule (blocked or random), task similarity (similar or dissimilar), and amount of practice on motor learning. Participants were required to perform three movement times (200, 350, and 500ms) in a blocked or random schedule while pointing towards the target located in the front direction in the similar condition, or towards three targets (left, front, and right) in the dissimilar condition. In each condition, participants completed 99 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…Usually, task material exploited in motor learning studies of music tend to be significantly more elaborated (melodic lines or excerpts of instrumental literature, often bimanual in the case of pianists) in order to reflect actual real-world demands of music motor behavior. Previous findings suggest that the effects of VOP may depend on the qualitative properties of the task in training and transfer (Healy et al, 2006; Boutin and Blandin, 2010). In addition to the nature of the task, several empirical accounts have indicated that the degree of complexity of a task is of crucial relevance (see Wulf and Shea, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, task material exploited in motor learning studies of music tend to be significantly more elaborated (melodic lines or excerpts of instrumental literature, often bimanual in the case of pianists) in order to reflect actual real-world demands of music motor behavior. Previous findings suggest that the effects of VOP may depend on the qualitative properties of the task in training and transfer (Healy et al, 2006; Boutin and Blandin, 2010). In addition to the nature of the task, several empirical accounts have indicated that the degree of complexity of a task is of crucial relevance (see Wulf and Shea, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is quite possible that sequence-specific benefits only emerge as practice is extended during which critical details of practiced movement sequences are extracted and stored (see Breslin, Hodges, Kennedy, Hanlon, & Williams, 2010). Clearly, conducting the present study with substantially greater training will allow this issue to be addressed for older adults as well as afford the opportunity to evaluate if RP also supports further behavioral gain via sequence-specific learning for individuals with PD (Boutin & Blandin, 2010).…”
Section: Probing the Learning Advantage From Greater Contextual Intermentioning
confidence: 98%
“…In line with this notion, Shea et al [22] proposed that the benefits of CI increased with increasing amounts of practice. This might suggest that a certain level of experience in a complex task is required in order to obtain benefit from randomized practice [22], [23].…”
Section: Introductionmentioning
confidence: 99%